Pengaruh Kegiatan Fun Cooking Terhadap Kemandirian Anak Usia 5-6 Tahun Di Tk Negeri Pembina Siborongborong (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This research aims to determine the effect of fun cooking activities on the independence of children aged 5-6 years at the Pembina Siborongborong State Kindergarten. The type of research used in the research is quantitative research with experimental research methods and the type of research design is one group pretest posttest design. The population in this study were all children aged 5-6 years at the Pembina Siborongborong State Kindergarten, totaling 66 people, and the sampling technique used purposive sampling, namely 22 children from class B2. Data collection techniques are carried out using observation sheets and documentation. Based on the recapitulation of data on children's independence before being given treatment (pretest) using fun cooking activities, there were 9.10% in the BSB category, 50% in the BSH category, 36.30% in the MB category, and 4.50% in the BB category. After being given treatment (post-test) using fun cooking activities, there were 54.50% in the BSB category, 45.40% in the BSH category, none in the MB and BB categories. From the results of the coefficient of determination test, the value r2 = 0.287, from the value of determination (r2) it can be seen that the percentage of influence of paper cutting activities on the fine motor skills of group A in GKPI Tarutung City Kindergarten is 28.7%. Furthermore, based on the results of the t test, the value of tcount ˃ ttable (6.638 ˃ 1.721) was obtained. So it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of fun cooking activities on the independence of children aged 5-6 years at the Pembina Siborongborong State Kindergarten.